2020
DOI: 10.1186/s12874-020-01064-1
|View full text |Cite
|
Sign up to set email alerts
|

Sources of potential bias when combining routine data linkage and a national survey of secondary school-aged children: a record linkage study

Abstract: Background: Linking survey data to administrative records requires informed participant consent. When linkage includes child data, this includes parental and child consent. Little is known of the potential impacts of introducing consent to data linkage on response rates and biases in school-based surveys. This paper assessed: i) the impact on overall parental consent rates and sample representativeness when consent for linkage was introduced and ii) the quality of identifiable data provided to facilitate linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Participants supported a central system for patients to control the uses of their data, and likewise a single NHS mechanism to sign up for active research participation. There is a trade-off between the scientific desirability of everyone contributing de-identified data, including to avoid bias,76 77 and the desirability of individual control over data use 78. As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research.…”
Section: Discussionmentioning
confidence: 99%
“…Participants supported a central system for patients to control the uses of their data, and likewise a single NHS mechanism to sign up for active research participation. There is a trade-off between the scientific desirability of everyone contributing de-identified data, including to avoid bias,76 77 and the desirability of individual control over data use 78. As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research.…”
Section: Discussionmentioning
confidence: 99%
“…We could simultaneously assess psychological factors, self‐harm and other physical/mental health related conditions using validated measures or codes to ensure validity and reliability. To circumvent selection/collider biases from using nonrepresentative samples (Griffith et al, 2020; Morgan et al, 2020), we applied IPW adjustment to the SHRN cohort by nesting it within a population‐based cohort (Griffith et al, 2020). We were able to analyse the associations of in‐person bullying victimization at school and cyberbullying victimization on future self‐harm separately and at the same time adjusted for other known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate potential biases of the SAIL‐linked SHRN cohort (Griffith et al, 2020; Morgan et al, 2020), we weighted the SHRN cohort by inverse probability weighting (IPW) based on propensity scores (PS) (Seaman & White, 2013). We first identified individuals from SAIL who were not from the survey sample and aged 11–16 years at the date of survey and then combined them with the SHRN cohort to form a large cohort representing the 11–16 years olds population of Wales (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In other contexts, researchers cannot access the large datasets that can be used for social and health-related research due to concerns around privacy and confidentiality. Current research topics related to these concerns revolve around privacy-preserving record linkage and understanding the bias introduced by the requirement for informed consent [ 26 , 27 ]. We turn to further discussion of the practical considerations around record linkage next.…”
Section: Methodologiesmentioning
confidence: 99%